Anteseden dari Pengungkapan Enterprise Risk Management pada Perusahaan yang Terdaftar di Indeks LQ45 - Rini, Keny Prasetyo; Zakiyah, Tuti (Institut Agama Islam Bengkulu, 2020)
The purpose of this research is to determine te influences of independent commissioners, auditor reputation, risk management committee, leverage and firm size on enterprise risk management disclosure in index LQ45 companies listed in the 2016-2018. The samplimg method in this research is purposive sampling with 81 companies as population and 27 companies as samples. The ERM practice is measured based on ERM index, which considers the eight dimension of ERM by COSO framework. The results of simultaneous regression analysis show that the variables of independent commissioner, auditor reoutation, risk manegement committee, leverage and firm size have positif effects on the enterprise risk management disclosure. Partial testing shows that variabel of independent commissioner, risk management commite and firm size does not effect enterprise risk management disclosure. Auditor reputation and risk management committee have positive effects on enterprise risk management.